TO THE QUESTION ABOUT THE SIMULATION OF TURBULENT THERMAL FLOWS - K. A. Zudov; M. A. Kudrov; G. Y. Tolkachev; K. I. Malyutkina (Научный вестник МГТУ ГА, 2016)
The main purpose of this work was the simulation of turbulent thermal flows, which is aimed at improving the visualization and the modeling of the flow fields of wind flows, which are necessary for aviation. The physical-mathematical model of gas flow in thermal is proposed on the basis of thermodynamic model and dynamic model under the assumption that the condensation energy, when the movement of the thermal is upward, becomes the turbulent fluctuations. A thermal is an air mass, which goes up and is capable to intermix with ambient air. In the work the thermodynamic model of thermal is presented, the equations and the system of equations are derived, that describe the main characteristics of wind flow, which are required for the modeling of airflows. The generation of vertical turbulent gust with von Karman spectrum is shown. The basic assumption in the construction of the dynamic model of generation was that the energy, which is stood out in the thermal due to the condensation of steam, is converted into the energy of turbulent pulsations. Some examples of numerical simulation are given in the article. The visualizations of the generation of the vertical velocity of random wind gust are given depending on the size of the considered space and depending on the pitch of cell partition. The analysis and comparison of the obtained results of the calculation are presented. The conducted studies are aimed at the simulation of the atmospheric background and atmospheric processes and, in the final result, at the increasing of flight safety.